L’efficacité du bilan de compétences - Michaud, Guylaine; Dionne, Patricia; Beaulieu, Ginette (Canadian Journal of Counselling and Psychotherapy, 2008)
There is convincing evidence of the effectiveness of a competency profile for beneficiaries. This approach is of significant benefit and usefulness to individuals who want to increase their self-knowledge, decide on future training, and develop a career plan. In the end, it is useful in recognizing an individual’s competencies. This type of approach has an impact on psychological processes, increasing self-esteem and self-awareness, helping define self-image more accurately, and increasing motivation for career planning. Finally,a competency profile can facilitate career transitions.